Horse Racing the Chicago Way : Gambling, Politics, and Organized Crime, 1837-1911. - Riess, Steven (Sports and Entertainment Ser., 2022)
""Horse Racing the Chicago Way" contextualizes the history of horse racing in Chicago, analyzing the role of political influence and class in the rise and fall of thoroughbred racing; the business of racing; the cultural and social significance of racing; and the impact widespread opposition to gambling in Illinois had on the sport. It also examines the nexus that existed between horse racing, politics, and syndicate crime"--